The Canadian Orthopaedic Trauma Society: lessons learned from 30 years of collaborative, high-impact research in fracture care. (1st May 2021) - Axelrod, Daniel; Trask, Kelly; Buckley, Richard E.; Johal, Herman
Abstract : Aims: This study reviews the past 30 years of research from the Canadian Orthopedic Trauma Society (COTS), to identify predictive factors that delay or accelerate the course of randomized controlled trials in orthopaedic trauma. Methods: We conducted a methodological review of all papers published through the Canadian Orthopaedic Trauma Society or its affiliates. Data abstracted included: year of publication; journal of publication; study type; number of study sites; sample size; and achievement of sample size goals. Information about the study timelines was also collected, including: the date of study proposal to COTS; date recruitment began; date recruitment ended; and date of publication. Results: In total, 22 studies have been published through the COTS working group, 13 of which are randomized controlled trials (RCTs). In total, 1, 423 individual patients have been involved in COTS studies, a mean of 110 patients per trial (22 to 424). Each study was conducted across a mean of approximately six centres (1 to 11) and took nearly ten years (mean 119.9 months (59 to 188)) from presentation of concept to publication. The mean length of enrolment was 63 months (26 to 113) and the mean time from cessation of enrolment to publication 51 months (19 to 78). Regardless of sample size, the only factor associated with a decreased length of enrolment was a higher number of clinical sites (p = 0.041). Neither study sample size nor length of enrolment were associated with total time to publication. Conclusion: Over the last three decades, COTS has developed a multinational strategy to produce high-quality evidence in the field of orthopaedic trauma through 13 multicentre RCTs. Future efficiencies can be realized by recruitment of more clinical sites, improving connectivity between the sites, and the promotion of national streamlined ethics processes. Cite this article: Bone Joint J  2021;103-B(5):898–901.